Occupation-specific social competences in vocational education and training (VET) : the example of a technology-based assessment - Monnier, Moana [Verfasser]; Tschöpe, Tanja [Verfasser]; Melzig, Christian [Verfasser]; Dietzen, Agnes [Verfasser] (My University, 2016)
"The difficulties regarding the definition and measurement of social competences, crucial to the research in vocational education and training, are well known. In this paper, we show, based on the example of medical assistants in Germany, that these skills have to be assessed in an occupation-specific way, and develop an appropriate simulation-based Situational Judgment Test. Competence modeling, the translation into the test format and results of a data collection are discussed in detail for the dimension of communicative strategies. Based on empirical and theoretical analysis, we derived a normative competence model underlying the development of a video-based situational judgment test. The final assessment contained 2 x 6 prototypical interactional types of situations, presented in short videos. At the end of every scene, questions of multiple choice format or open questions were asked for each of the social competence dimensions (emotion regulation, perspective coordination, communication strategies). In regard to the evaluation, for the dimension of communication strategies, for example, open answers were rated by using a weighted checklist giving a final score for each situation or all over the test. After two pre-evaluations on N = 236 and N = 260 pupils at the end of their apprenticeship towards becoming medical assistants, validity aspects due to e.g. format were analyzed and edited. A final inquiry on N = 405 pupils confirmed the expected reliability and dimensionality aspects." (Authors' abstract, BIBB-Doku)
Keywords: L 8 Diagnostik / Eignung; L 6.3.1 Diagnose- & Messinstrumente; Kompetenzforschung; Sozialkompetenz; Medizinischer Fachangestellter; Kompetenzdiagnostik; Kompetenzfeststellung; Kompetenzmodell